Medial Vowel Temporal Acoustics in Arabic and Japanese Polysyllabic Words - ALDHOLMI, Yahya (Archives of Acoustics, 2022)
The current study is dedicated to measuring vowel temporal acoustics (duration, durational difference, and durational ratio) in the medial position of mostly CVCVCV polysyllabic words in Arabic and Japanese, avoiding the asymmetries in vowel position, syllable structure, and coda consonant quantity (singleton versus geminate) observed in previous experiments. Twenty-nine (16 Arabic and 13 Japanese) participants were asked to use a carrier sentence to produce 60 polysyllabic (mainly CVCVCV) items that contrasted in vowel quantity (short versus long) and vowel quality (/a/, /i/, and /u/) at a normal speech rate. The results show that while short and long vowels are durationally distinct within a language, Japanese vowels are clearly longer than Arabic vowels, although the durational difference remains approximately the same between the two languages. The durational ratio of short-to-long vowel presents a new pattern that contrasts with that reported in earlier research. Specifically, Japanese long vowels in the medial position of polysyllabic words are twice as long as their short counterparts, while Arabic long vowels are more than twice as long. This shows that both vowel position and syllable structure must be considered when measuring vowel temporal acoustics or when structuring stimuli for perception experiments.